Mini-review: Utilization of Vibrio parahaemolyticus virulence coding genes for early detection of acute hepatopancreatic necrosis disease (AHPND) - Munti Yuhana; Usamah Afiff (Jurnal Akuakultur Indonesia)
The ability to track the presence of pathogenic Vibrio parahaemolyticus, an AHPND causative agent in shrimp is one of the keys to controlling this infectious disease. A reputable disease diagnosis is appreciated as the ability to track the pathogenic infection when the host abnormality is undetectable due to the low pathogenic cell concentration. This mini-review article discusses the selected virulence encoding genes as molecular markers and the steps of standard validation methods in the application for early detection of AHPND disease. The proper diagnosis method is crucial to prevent the spread of Vibriosis AHPND which significantly results in economic losses for shrimp farmers. In this early warning system, we need a molecular method available for quick detection by applying the tracking tools that can discriminate pathogenic V. parahaemolyticus AHPND strain. Several types of potential genes that can be developed into tracking devices for infectious Vibriosis are pathogenic genes encoding the virulence factor. Through several stages of testing the selected virulence encoding genes will be developed into molecular markers. The polymerase chain reaction method and several of its variants have been widely applied using selected molecular markers. Furthermore, the use of molecular markers for the diagnosis of AHPND disease in shrimp must be validated by determining aspects of sensitivity, detection specificity, repeatability consistency, and reproducibility